Exploring Pillar[6]quinone as Cathode Material for Aqueous Zinc-Ion Batteries - Yeşilot, Serkan; Kilic, Nazmiye; Sariyer, Selin; Solmaz, Yasemin; Guner, Merve; Demir-Cakan, Rezan (Wiley-V C H Verlag Gmbh, 2025)
Quinone cathodes have wide application prospects in aqueous zinc-ion batteries (AZIBs) due to their high performance, structural diversity, sustainability, high specific capacity, and fast reaction kinetics. Herein, pillar[6]quinone (P6Q), a member of the quinone group, is used as a cathode in AZIBs for the first time. The P6Q structure consisting of six benzoquinone units with a higher cavity than the quinone structures with small molecule structures is found to greatly improve the cycling stability of the cathode. The P6Q electrode exhibits remarkable electrochemical stability and a long-term cycle life (discharge capacity of 118 mAh g-1 and capacity retention of 83% after 10 000 cycles at current density of 50C). In addition, density functional theory calculations and ex situ characterization methods such as ultraviolet-visible spectroscopy, X-ray photoelectron spectroscopy, and Fourier-transform infrared spectroscopy are used to clarify the possible coordination mechanism between P6Q and Zn2+/H+ ions.
Keywords: aqueous zinc batteries; organic cathode materials; pillar[n]quinone